El corazón de la mujer - Arocha R., J. Ildefonzo (Revista Hospital Clínico Universidad de Chile, 2019)
In the vast majority of cardiovascular diseases (CVDs), there are well-described differencesbetween women and men in epidemiology, pathophysiology, clinical manifestations, effects oftherapy, and outcomes. These differences arise on one hand from biological differences amongwomen and men, which are called sex differences, due to differences in gene expression fromthe sex chromosomes and subsequent differences in sexual hormones leading to differencesin gene expression and function in the CV system, In contrast, gender differences are uniqueto the human. They arise from sociocultural processes, such as different behaviours of womenand men; exposure to specific influences of the environment; different forms of nutrition,lifestyle, or stress; or attitudes towards treatments and prevention. The scientific societiesare at the forefront of implementing the knowledge in research and healthcare strategies withmore proactive attitude for a feminine centered approaches may lead to a more specific andeffective use of resources in CVD prevention and therapy in women.